Do Low-Income Housing Tax Credit Developments Expand Neighborhood Opportunities? - Yongjin Ahn; Jongho Won (Buildings)
Living in deprived neighborhoods not only reflects a lack of social networks, role models, and safety, but also indicates limited access to local establishments that provide daily necessities—all of which are crucial for residents’ social mobility. The Low-Income Housing Tax Credit (LIHTC) program—the most influential place-based housing assistance initiative in the United States (U.S.)—is one such program that strives to achieve this challenging goal. However, studies have shown that LIHTC units are often constructed in socioeconomically disadvantaged neighborhoods. Therefore, this study investigates the spillover effects of LIHTC developments on neighborhood resource availability that is essential not only for immediate well-being but also for fostering long-term social mobility. This study employed the propensity score method, the inverse probability treatment weight, and weighted linear regression to address the selection bias problem of developers’ site decision. This study finds that a neighborhood that received LIHTC development between 2010 and 2015 experienced a greater increase in the number of employees in grocery stores, healthcare providers, job-training centers, libraries, pharmacies, and recreational centers from 2010 to 2016 than neighborhoods without LIHTC developments during the same time. The significance of this study lies in its analysis of the effects of LIHTC projects on physical facilities while accounting for self-selection bias.